Absorptive capacity in strategic management: evidence from digital technology-based SMEs - Marcio Augusto Lassance Cunha Filho; Cristiane Drebes Pedron; Roberto Lima Ruas (Revista de Ciências da Administração : RCA)
Objective of the study: This study aims to determine how organisational absorptive capacity (ACAP) component elements are embedded in the strategic management processes of digital technology-based small and medium-sized enterprises (digital SMEs).